1997
DOI: 10.1523/jneurosci.17-20-07754.1997
|View full text |Cite
|
Sign up to set email alerts
|

Neurons Promote the Translocation of Peripheral Myelin Protein 22 into Myelin

Abstract: Schwann cells express low levels of myelin proteins in the absence of neurons. When Schwann cells and neurons are cultured together the production of myelin proteins is elevated, and myelin is formed. For peripheral myelin protein 22 (PMP22), the exact amount of protein produced is critical, because peripheral neuropathies result from its underexpression or overexpression. In this study we examined the effect of neurons on Schwann cell PMP22 production in culture and in peripheral nerve using metabolic labelin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
196
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 141 publications
(217 citation statements)
references
References 49 publications
16
196
0
Order By: Relevance
“…In DMSO carrier-treated cells, PMP22 is detected at low levels in the ER and Golgi apparatus, and at the plasma membrane (Fig. 5A, DMSO inset, also see Pareek et al, 1997). When simultaneous to proteasome inhibition, autophagy is enhanced (starvation, Stv), fewer cells form aggregates (Fig.…”
Section: The Formation Of Aggresomes Is Hindered By Autophagymentioning
confidence: 88%
See 1 more Smart Citation
“…In DMSO carrier-treated cells, PMP22 is detected at low levels in the ER and Golgi apparatus, and at the plasma membrane (Fig. 5A, DMSO inset, also see Pareek et al, 1997). When simultaneous to proteasome inhibition, autophagy is enhanced (starvation, Stv), fewer cells form aggregates (Fig.…”
Section: The Formation Of Aggresomes Is Hindered By Autophagymentioning
confidence: 88%
“…In non-myelinating and myelinating SCs, the majority (~80%) of the newly-synthesized PMP22 is rapidly degraded by the UPS, presumably due to misfolding (Pareek et al, 1997). Mutations in PMP22, or duplication of the PMP22 gene, are associated with hereditary demyelinating neuropathies among which, Charcot Marie Tooth type 1A (CMT1A) is the most common form (Young and Suter, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…1 and step 1a), may be refolded by molecular chaperones at the endoplasmic reticulum (ER) 13 ( Fig. 1 and step 2).…”
Section: The Proteasome and Aggresome-autophagy Pathways Protect Schwmentioning
confidence: 99%
“…1 and step 5) that inhibit proteasome function ( Fig. 1 and step 6 ) and may impair Schwann cell functions including myelination 13,14 ( Fig. 1 and step 7).…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%
“…For Western blotting, monolayers of confluent MDCK cells were lysed (Notterpek et al, 2001), and where indicated, treated with N-glycosidase (PNGase F) (Pareek et al, 1997). Samples were separated by SDS-PAGE and transferred to nitrocellulose membrane (Bio-Rad, Hercules, CA) before immunoblotting.…”
Section: Cell Surface Biotinylation and Western Blottingmentioning
confidence: 99%